Peer Interaction Patterns Among Eighth Grade Students at Sinar Husni Helvetia Junior High School - Salva Khairani; Sakti Ritonga (Journal of General Education and Humanities, 2025)
This study aims to describe the forms, patterns, and dynamics of peer interactions among eighth-grade students at Sinar Husni Helvetia Private Junior High School, and to analyze their impact on students' social and emotional development. The background of this study stems from the importance of peer relationships as a key factor in the formation of adolescents' social personality, especially in a school environment that is socially and culturally heterogeneous. This study employs a descriptive qualitative approach, utilizing data collection techniques that include participatory observation, in-depth interviews, and documentation. Research informants include eighth-grade students, homeroom teachers, subject teachers, and guidance counselors, who were selected through purposive sampling techniques. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing with validation through source, technique, and time triangulation. The results of the study show that students' forms of social interaction include both associative interactions (cooperation, accommodation, and assimilation) and dissociative interactions (competition and contravention) at low intensity. Students' strategies in establishing and maintaining friendships are demonstrated through empathy, open communication, tolerance, and the ability to adapt to differences in friends' personalities. Positive interaction patterns are proven to influence increased self-confidence, adaptability, and emotional balance in students, while negative interactions, such as group exclusivity or teasing, can lead to social awkwardness and low self-esteem.